Examining the behavioural intention to save in a voluntary retirement fund in Malaysia - Yusof, Radduan; Sabri, Mohamad Fazli; Abd. Rahim @ Abd. Wahab, Husniyah; Md Jusoh, Zuroni (Malaysian Consumer and Family Economics Association, 2018)
This study utilised the Decomposed Theory of Planned Behaviour (DTPB) to examine the intention to save in voluntary retirement funds in Malaysia. Three hundred and thirty-four (n=334) usable samples were obtained via a purposive multistage cluster sampling technique. The data was analysed to assess the determinants predicted by the DTPB through structural equation modelling using the PLS-SEM. The results revealed that attitude, subjective norms, and perceived behavioural controls have significant effects on a person‟s intention to save in a voluntary retirement fund, albeit to a varying degree. The path analysis indicated perceived behavioural controls as the strongest predictor, followed by attitude and subjective norms. These three constructs explain 58% of the variance in the intention to save in a voluntary fund. When the model in this study further analysed the antecedents of attitude, it found that the relative advantages positively influenced attitude, compatibility had a negative influence, and complexity had no significant value. With regards to subjective norms, both external and internal norms significantly influenced the construct. Finally, both self-efficacy and facilitating conditions had significant effects towards perceived behavioural controls. Predicting a person‟s intention to save in a voluntary retirement fund is an important issue and the findings of this study would have practical implications on policy makers and commercial marketers alike, as it would help to encourage retirement savings through voluntary funds to prevent financial insufficiency in the golden age.